PARTICIPATORY APPROACH TO EXTENSION EDUCATION: A TOOL FOR ACHIEVING SUSTAINABILITY OF FOREST IN YOBE STATE, NIGERIA (AUN INTERNATIONAL CONFERENCE, 2024)
Despite understanding the roles and contributions of forest extension workers in literature of management of forests in Sub-Saharan Africa, the forests in Northern Nigeria continue to deteriorate in size and composition, and literatures on suitable methods of forest extension and education is limited. This study aimed to examine the characteristics of the methods of forest extension and education in Yobe The objectives of the study therefore are to identify the characteristics of the methods of forest extension and education and assess the level of acceptability of the methods used in the transmission of information on sustainable forest management by forest extension and education workers in Yobe, Nigeria. Data were collected from 150 purposively selected respondents across the three randomly selected local government councils in Yobe, Nigeria. The data were analyzed using descriptive statistics, a general linear mixed model, and thematic analysis. The results identified five methods used in passing information on sustainable forest management to forests beneficiaries in the state namely the social (local leader) method, the community approach, the traditional group method, the social situation method, and the traditional individual approach. The social (local leader) method was the most acceptable method due to its characteristic reliability and fairness. The result from the modelling that regressed five predictor variables shows the social (local leaders) approach and the community approach as the predictors identified within the model that had the lowest Akaike’s Information Criterion value of 157.8 and adjusted R2 value of 26.8%. The adjusted R-squared value indicated that 73.2% of the people’s opinions could not be explained by this model. This study highlights the ways to improve people’s livelihood and identifies important indicators to enhance forest extension and education to achieve forests sustainability in Yobe. The results will provide information to policymakers in developing policy on the economic, social, and environmental benefits of forest. The study recommends policy measures aimed at inclusion of local leaders in the sustainable management of forests.